Do Forms of Knowledge Production Circulate? Argentinian Anthropologists in the Master’s and PhD Programs in Social Anthropology at the National Museum of the Federal University of Rio de Janeiro (PPGAS-MN/UFRJ) - Isola, Nicolás José (Serendipities. Journal for the Sociology and History of the Social Sciences, 2020)
Forms of knowledge production adopted by academics in a given national space do not emerge without the right circumstances. Student circulation has a bearing on knowledge import processes. Opening with an overview of the field of Argentinian anthropology in the 1970s and 1980s, this article looks at some of the consequences of the international circulation of Argentinian students through the Social Anthropology Master’s and PhD Programs at the National Museum of the Federal University of Rio de Janeiro (PPGAS-MN/UFRJ) from the late 1980s to the present. Based on documents in the PPGAS-MN archives, interviews with lecturers and former students and a review of PPGAS-MN and Argentinian university syllabi, this article: (i) provides a historical description of the agreement between institutions that has facilitated this flow; (ii) describes how this circulation has given these students a new perspective on the ethnographic approach and on classical anthropology; and (iii) describes how, from a student viewpoint, this shift has altered their way of thinking about social anthropology research and given them a new habitus. The results hint at a new approach to classical anthropology and the use of ethnographic data. There were three main drivers: (i) PPGAS-MN lecturers’ emphasis on the relevance of empirical data and the primacy of theory prevailing in Argentina; (ii) the renewed deep reading of classic ethnographical texts; and (iii) the development of a new habitus as a result of socialisation in the ensuing social space.